Peran Keluarga dalam Mencegah Tuberkulosis Paru - Radandima, Ester; Toru, Veronika; Mila, Antonetha R H (JURNAL KESEHATAN PRIMER, 2021)
Background:  Mycobacterium tuberculosis bacteria cause pulmonary tuberculosis, which attacks the lungs and can spread through air droplets from people who cough or sneeze. In many countries, especially Indonesia, which has a fairly high burden of TB cases, this disease is still a major health problem. Apart from environmental factors and health services, family factors are very important in preventing and treating pulmonary TB. It is very important for families to help infected family members get the right treatment and maintain a healthy home environment. Method: The research design used was quantitative with a descriptive approach. Participants were selected using a purposive sampling/total sampling technique, using a questionnaire sheet distributed to respondents and an observation sheet held by the researcher. The research sample was twelve people who met the inclusion and exclusion criteria. Results: In this study, 8 people (66.67%) obtained roles in general with a sufficient role category.